Peran Guru PAI dalam Menanamkan Karakter Islami di MIM Kluwih II - Setiowati, Sri; Hamdani, Mohammad Khusnul (ALSYS, 2025)
The problems that occur and are the topic of this research are based on the increasingly declining morals and Islamic character of the younger generation which are increasingly being eroded by the current of developments over time. This research aims to determine the instillation of character values based on Al-Islam and Muhammadiyah Education at the MI Muhammadiyah Kluwih II school. This research uses qualitative research methods. Objects used at MIM Kluwih II. With research subjects, class VI students and PAI MIM Kluwih II Pacitan teachers. Data collection uses observation and interview techniques. These two techniques are used to check the validity of research data and information. The results of this research state that the role of Islamic Religious Education Teachers in instilling Islamic character values at MIM Kluwih II is knowing the role of Islamic Religious Education Teachers as mentors, as educators, as motivators, as evaluators and as role models, and being able to identify inhibiting factors for Islamic Religious Education Teachers in instilling Islamic character values, namely differences in students' lack of interest in participating in religious activities, the influence of the school environment, family environment and society which can influence the level of participation, behavior and personality of students. Islamic Religious Education Teachers consistently play a role in provide encouragement to students to accept and practice Islamic character values. Islamic Religious Education Teachers carry out coaching by implementing habits such as smiling, greetings, greetings, being polite, polite, reading prayers and the Asmaul Husna before and after learning, every time they perform the dhuha prayer, muroja'ah juz 30, and carry out midday prayers in congregation.